Towards communities open to diversity and innovation: the role of Muslim women - Di Santo, Patrizia; Lombardi, Milena (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The Islamic terrorist attacks in Europe has fueled a negative sentiment towards Muslim citizens, subject to discrimination for a faith deemed incompatible with western values. The greater the impact on women, whom the stereotype sees as submissive and without freedom of choice. The LADIS Local Administrations against Stereotypes and ISlamophobia project aims to encourage the development of local policies for the prevention and contrast of discrimination against Muslims, especially against women. Model to be replicated and developed for increasingly supportive communities, open to diversity and innovation, capable of responding to the cultural and social crisis amplified by the pandemic.